Spontaneous resolution in congenital nasolacrimal obstruction after 12 months - Schellini, Silvana Artioli [UNESP]; Capanema, Sara [UNESP]; Ribeiro, Ferreira [UNESP]; Jaqueta, Elizângela [UNESP]; Padovani, Carlos Roberto [UNESP]; Roberto, Carlos [UNESP]; Padovani, Pereira [UNESP] (Taylor & Francis, 2007)
A retrospective observational study was performed in order to evaluate the possibility of spontaneous resolution of tearing in the congenital nasolacrimal obstruction (CNLO). Twenty-seven CNLO child carriers with spontaneous tearing resolution were evaluated according to sex, age of starting and end of symptoms. The data were evaluated by the Chi-Square Test and non-parametric Mann-Whitney test (p ≤ 0.05). Spontaneous resolution occurred between ages 3 and 48 months (Median = 14 months; Mean = 16.2 ± 10.5 months). The period in which the child presented tearing varied from 2 months to 47.5 months (Median = 12 months) and was similar for both sexes, with or without realization of massage. Our data support the possibility of CNLO spontaneous resolution in children beyond 12 months of age, allowing us to suggest postponed probing beyond this time period. Copyright © Informa Healthcare.
Keywords: Children; Congenital nasolacrimal obstruction; Spontaneous resolution; Tearing; chi square test; clinical article; female; human; infant; lacrimal duct occlusion; male; massage; preschool child; priority journal; rank sum test; retrospective study; Child, Preschool; Female; Humans; Infant; Lacrimal Apparatus Diseases; Lacrimal Duct Obstruction; Male; Nasolacrimal Duct; Remission, Spontaneous; Retrospective Studies; Tears; Time Factors